The art of strategy : Sun Tzu, Michael Porter, and beyond - Mun, Hwi-chʻang (Cambridge : Cambridge University Press, 2018)
When it comes to strategy, how should we define victory? For centuries, Eastern and Western thinkers have grappled with this question, offering different answers. What can we learn from this difference? In The Art of Strategy, Moon provides a novel and systematic integration of the two dominant frameworks of the East and West: Sun Tzu's military strategy and Michael Porter's business strategy. This unlikely combination of thinking suggests an innovative extension of our understanding and practice of strategy, which will appeal to scholars, students, practitioners and general readers with an interest in strategy. By aligning the perspectives of these two great thinkers, Moon argues that true winning is about maximizing and optimizing overall value for all engaged stakeholders, and this requires a more efficient approach to strategy.
Title from publisher's bibliographic system (viewed on 01 Aug 2018).
Keywords: Strategic planning; Management; Military strategy; Porter, Michael E., -- 1947-; Sunzi, -- active 6th century B.C.